Factors Influencing Green Practices Adoption and Infusion by Manufacturing Companies in Ogun State, Nigeria - Oludele Mayowa Solaja; Obatunde Bright Adetola; Emeka E. Okafor (Sriwijaya Journal of Environment, 2020)
This study examined factors influencing the adoption and infusion of green practices by manufacturing companies in Ogun State, Nigeria. The study adopted a cross-sectional and descriptive survey research design. Area-based technique in which multi-stage sampling technique was used to select 321 employees of medium and large-sca2le manufacturing firms in Ogun State, Nigeria. A semi-structured questionnaire was used for data collection. The data were analysed using factor analysis and multiple regression. An examination of the research objective revealed two technological factors which are a combination of adoption cost and complexity (as the first factor) as well as the combination of relative advantage and compatibility (as the second factor) that influence green practices adoption in every manufacturing company. Also, five organizational factors (regulatory support, organizational support, quality of human resources, environmental factors and customer pressure) influence green practices adoption with eigenvalues greater than 1 and Cronbach’s alpha greater than 0.700. Test of hypotheses revealed that compatibility (β =0.191, t = 2.033; P < .05), organizational support (β = -0.303, t = -3.595; P < .05), environmental factors (β = -0.219, t = -3.199; P < .05) significantly independently predicted infusion of green practices while, adoption cost (β =-0.087, t = .909; P >.05), complexity (β =0.022, t = .264; P < .05), relative advantage (β =0.072, t = 808; P > .05), quality of human resource (β =0.125, t = 1.364; P > .05), government support (β =-.031, t = -464; P > .05), regulatory support (β = -.118, t = -1.562 P > .05) and customer pressure (β = -.119, t = -1.557; P > .05) had no significant independent prediction on infusion of green practices. The findings of the study were discussed within the existing literature and recommendations were provided for policy intervention.